A feature–based approach to an integrated CAD/CAPP system in sheet metal blanking dies. (1st December 2014) - Nasr, Emad S. Abouel; Hussein, H.M.A.; Ragab, Adham E.; Kamrani, Ali K.
Computer–aided process planning (CAPP) is considered to be the bridge that links computer–aided design (CAD) and computer–aided manufacturing (CAM). This paper describes a new approach to introduce computer–aided process planning into sheet metal blanking dies industry. The proposed system consists of two modules which are the CAD module and CAPP module. The first module is capable of reading 2D drawings of sheet metal parts provided by AutoCAD software, extracting geometric data from the drawings, building a die geometry that would produce the sheet metal part, and producing solid models of each die component. The second module receives the 3D blanking die components in IGES format and applies an intelligent feature extraction methodology in order to extract their manufacturing characteristics and produce a machining plan for each component. The proposed system is limited to prismatic die components. Finally, a case study is presented for demonstration purposes.